2005
DOI: 10.1111/j.1365-2265.2005.02348.x
|View full text |Cite
|
Sign up to set email alerts
|

SRD5A2 gene analysis in an Italian population of under‐masculinized 46,XY subjects

Abstract: This first report of an Italian population underlines the importance of differential diagnoses in patients with under-masculinization. The lack of precise genotype-phenotype correlation in some of the mutations highlights the necessity to improve knowledge about the biochemical aspects of steroid 5alpha-reductase action and about the interactions of genetic and environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 20 publications
4
51
2
Order By: Relevance
“…As in the present girl the lack of appropriate endocrine investigation before gonadectomy did not provide indications for genes to be investigated, unsuccessful analysis of the AR gene was performed before screening of SRD5A2 , which permitted the identification of compound heterozygosity. The Q126R mutation we found in exon 2 has been previously reported in several patients from different countries [Wilson et al, 1993;Hackel et al, 2005], but it has not yet been described in Italian patients [Nicoletti et al, 2005;Bertelloni et al, 2007;Baldinotti et al, 2008]. This mutation is located in a highly conserved region of type 2 enzyme [Hackel et al, 2005] and its pathogenic role was confirmed by site-directed mutagenesis and in vitro assays [Wigley et al, 1994].…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…As in the present girl the lack of appropriate endocrine investigation before gonadectomy did not provide indications for genes to be investigated, unsuccessful analysis of the AR gene was performed before screening of SRD5A2 , which permitted the identification of compound heterozygosity. The Q126R mutation we found in exon 2 has been previously reported in several patients from different countries [Wilson et al, 1993;Hackel et al, 2005], but it has not yet been described in Italian patients [Nicoletti et al, 2005;Bertelloni et al, 2007;Baldinotti et al, 2008]. This mutation is located in a highly conserved region of type 2 enzyme [Hackel et al, 2005] and its pathogenic role was confirmed by site-directed mutagenesis and in vitro assays [Wigley et al, 1994].…”
Section: Discussionsupporting
confidence: 49%
“…To explain the presence of the Q126R mutation in different populations, the existence of a common ancestor spreading the mutation across Europe and then in South America has been suggested, although the possibility of a hotspot cannot be excluded [Hackel et al, 2005]. The mutation H230P in exon 4 was not previously reported in Italian patients with 5 ␣ -reductase-2 deficiency [Nicoletti et al, 2005;Bertelloni et al, 2007;Baldinotti et al, 2008]. However, it has been first identified in an Italian-American boy from New York, who was a compound heterozygote for N193S and H230P [Saenger et al, 1978;Wigley et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have shown that a significant proportion (41%) of 46XY DSD females have SRD5A2 deficiency and that this diagnosis should be considered for individuals labelled as PAIS, particularly, but not exclusively, those that virilise post-puberty. A similar prevalence of SRD5A2 mutations has been reported in a paediatric population of 46XY under-masculinised children (19), making this condition a more prominent component of the DSD population than previously considered.…”
Section: Discussionmentioning
confidence: 52%
“…A previous study revealed that the p.R246Q mutation decreases binding affinity for the nicotinamide adenine dinucleotide phosphate (NADPH) cofactor by disrupting the 5α-reductase type 2 enzyme and changing the optimal reaction pH [20]. The p.R246Q mutation is one of the most common mutations and has been identified in patients of various ethnic backgrounds including African-American, Pakistani, Italian, Austrian, Dominican, Brazilian, Egyptian, and Indian groups [8,21,22,23,24,25]. …”
Section: Discussionmentioning
confidence: 99%